Effect of Seed Source on Seed Vigour and Field Performance of the Sorghum [Sorghum bicolor. (L.) Moench] Cultivar Taba (University of Khartoum Journal of Agricultural Sciences, 2023)
A set of laboratory tests and field experiments were conductedfor two consecutive seasons (2009/10 and 2010/11) to investigate theeffect of seed source on seed quality attributes of the sorghum cultivarTabat. Simple correlation coefficients were calculated to determine thedegree of association between the different vigour tests and seedlingemergence under field conditions. Seeds were obtained from fourlocations: two rainfed (Damazin and Habeela) and two irrigated (KhashmEl Girba and El Gezira). Data were collected on initial seed moisturecontent, 1000-seed weight, germination percentage, rate of germination,seedling shoot length, seedling root length, seedling shoot to root lengthratio, seedling fresh weight, seedling dry weight, plant height, number ofleaves per plant, leaf area per plant and plant fresh and dry weight. Theresults indicated that, under laboratory conditions, seed source hadsignificant effect on seedling root length and fresh weight in the firstseason, on germination percentage and rate of germination in the secondseason and on seed moisture content and 1000 seed weight in bothseasons. Significant differences were found in seedling shoot length andplant height under field conditions. Seeds from Habeela and Damazinperformed well with regard to germination percentage, rate ofgermination and field seedling emergence. Also, seeds from the rainfedareas produced taller plants than those from irrigated areas (Khashm ElGirba and El Gezira). The results also showed that field seedlingemergence was positively correlated with the estimate, under laboratory